Activation of transient receptor potential vanilloid 1 by lipoxygenase metabolites depends on PKC phosphorylation. Issue 3 (16th December 2016) - Kumar, Rakesh; Hazan, Adina; Geron, Matan; Steinberg, Rebbeca; Livni, Lital; Matzner, Henry; Priel, Avi
ABSTRACT: Peripheral neuronal activation by inflammatory mediators is a multifaceted physiological response that involves a multitude of regulated cellular functions. One key pathway that has been shown to be involved in inflammatory pain is Gq/GPCR, whose activation by inflammatory mediators is followed by the regulated response of the cation channel transient receptor potential vanilloid 1 (TRPV1). However, the mechanism that underlies TRPV1 activation downstream of the Gq/GPCR pathway has yet to be fully defined. In this study, we employ pharmacological and molecular biology tools to dissect this activation mechanism via perforated‐patch recordings and calcium imaging of both neurons and a heterologous system. We showed that TRPV1 activity downstream of Gq/GPCR activation only produced a subdued current, which was noticeably different from the robust current that is typical of TRPV1 activation by exogenous stimuli. Moreover, we specifically demonstrated that 2 pathways downstream of Gq/GPCR signaling, namely endovanilloid production by lipoxygenases and channel phosphorylation by PKC, converge on TRPV1 to evoke a tightly regulated response. Of importance, we show that only when both pathways are acting on TRPV1 is the inflammatory‐mediated response achieved. We propose that the requirement of multiple signaling events allows subdued TRPV1 activation to evoke regulated neuronal response during inflammation.—Kumar R., Hazan, A., Geron, M., Steinberg, R., Livni, L., Matzner, H., Priel, A. Activation of transient receptor potential vanilloid 1 by lipoxygenase metabolites depends on PKC phosphorylation. FASEB J. 31, 1238–1247 (2017). www.fasebj.org